2004
DOI: 10.1167/iovs.04-0083
|View full text |Cite
|
Sign up to set email alerts
|

H-7 Effect on Outflow Facility after Trabecular Obstruction Following Long-Term Echothiophate Treatment in Monkeys

Abstract: H-7 can enhance OF in the presence of trabecular obstruction produced by long-term ECHO treatment. This suggests that H-7 may be useful in treating glaucoma, even in the presence of accumulated plaque material that has been described previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In support of this role, when human or monkey organ cultured anterior segments were perfused with the Heparin II binding domain or a PRARI peptide that activates α4β1 integrin signaling, outflow facility was increased (Santas et al, 2003; Gonzalez et al, 2009) and an expansion of the TM reminiscent of actin disrupting agents was observed (Gabelt et al, 2004, 2006; Schwinn et al, 2010). Interestingly, expression of the α4 integrin subunit is increased in the ONH in glaucomatous eyes (Morrison, 2006).…”
Section: Biological Processes Regulated By Integrinsmentioning
confidence: 97%
“…In support of this role, when human or monkey organ cultured anterior segments were perfused with the Heparin II binding domain or a PRARI peptide that activates α4β1 integrin signaling, outflow facility was increased (Santas et al, 2003; Gonzalez et al, 2009) and an expansion of the TM reminiscent of actin disrupting agents was observed (Gabelt et al, 2004, 2006; Schwinn et al, 2010). Interestingly, expression of the α4 integrin subunit is increased in the ONH in glaucomatous eyes (Morrison, 2006).…”
Section: Biological Processes Regulated By Integrinsmentioning
confidence: 97%
“…The drug is available under several trade names such as phospholine iodide. Adverse effects include muscle spasm and other systemic effects [112]. …”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…In nonhuman primate eyes, long-acting cholinesterase inhibitors such as echothiophate iodide have been shown to cause an increase in IOP, collapse and densification of the trabecular meshwork, alterations in the shape and orientation of Schlemm’s canal and the ciliary muscle, and discontinuity between ciliary muscle bundles and trabecular beams (Gabelt, Hennes, Seeman, Tian and Kaufman, 2004;Lutjen-Drecoll and Kaufman, 1986). Chronic echothiophate use also results in a decreased accommodative response to pilocarpine (Croft, Kaufman, Erickson-Lamy and Polansky, 1991).…”
Section: Introductionmentioning
confidence: 99%